Fundamentals of organic chemistry - McMurry, John (Brooks/Cole, Cencage Learning, 2011)
New concepts are introduced only when needed, frequent cross references are provided to earlier material, and numerous summaries are included to help draw material together. New problems have been added at the end of each chapter